2021
DOI: 10.3390/biology10040298
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Lipids and Fatty Acids: 3 Years Postoperative Laparoscopic Sleeve Gastrectomy

Abstract: Visceral obesity is common in the United Arab Emirates and worldwide. Although laparoscopic sleeve gastrectomy (LSG) leads to effective and sustainable weight loss, its long-term beneficial impact on other risk factors, including blood lipid and fatty acid (FA) profiles, remains unknown. These two profiles were assessed in patients 3 years after undergoing LSG and in LSG candidates (controls). Lipid profiles were measured using the Cobas e411 modular analyzer, and 35 FAs were identified. The age and body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Such clinically beneficial characteristics of changes in the lipid profile occurring after bariatric procedures is also described by many other authors studying the issue [20][21][22]. Regarding the average concentration of HDL-C lipid fractions and triglycerides in the plasma of analyzed patients obtained at the end of the observation and the criteria for diagnosing metabolic syndrome, it should be noticed that a decrease in the TG level below the threshold value of 150 mg/dL was obtained; however, the concentration of HDL-C increased above the desired amount of 50 mg/dL, so this procedure proved to be effective in the treatment of dyslipidemia defined by the criteria for metabolic syndrome.…”
Section: Discussionsupporting
confidence: 56%
“…Such clinically beneficial characteristics of changes in the lipid profile occurring after bariatric procedures is also described by many other authors studying the issue [20][21][22]. Regarding the average concentration of HDL-C lipid fractions and triglycerides in the plasma of analyzed patients obtained at the end of the observation and the criteria for diagnosing metabolic syndrome, it should be noticed that a decrease in the TG level below the threshold value of 150 mg/dL was obtained; however, the concentration of HDL-C increased above the desired amount of 50 mg/dL, so this procedure proved to be effective in the treatment of dyslipidemia defined by the criteria for metabolic syndrome.…”
Section: Discussionsupporting
confidence: 56%
“…Such clinically beneficial characteristics of changes in the lipid profile occurring after bariatric procedures is also described by many other authors studying the issue [20,21,22]. Regading the average concentration of HDL-C lipid fractions and triglycerides in the plasma of analyzed patients obtained at the end of the observation tand the criteria for diagnosing metabolic syndrome, it should be noticed that the decrease of TG level below the threshold value of 150 mg/dl was obtained, however, the concentration of HDL-C incrased above the desired 50 mg/dl, so this procedure proved to be effective in the treatment of dyslipidemia defined by the criteria of the metabolic syndrome.…”
Section: Beforesupporting
confidence: 56%
“…Sharma et al, conducted a study involving 134 patients with similar characteristics, out of which 71 underwent LSG, while the remaining 63 were followed up as the control group. After a 3-year follow-up, they found a significant (P<0.01) decrease in plasma triglyceride levels and a significant (P<0.001) increase in HDL-cholesterol levels among those who underwent LSG compared to the control group [21]. In a systematic review involving 3997 patients, Shabbir et al, demonstrated that LSG had a significant effect on HDL-cholesterol and triglyceride levels, while it did not show a significant impact on LDL-cholesterol levels [22].…”
Section: Original Articlementioning
confidence: 97%